(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
With the introduction of Islam in Movarounnahr, religious education and related sciences began to develop. Especially, religious and secular sciences developed organically. It was from this period that schools and madrasahs began to appear in the regions. In this article, valuable information about the establishment of madrasas and the source studies of the educational system in Movarounnahr in the first three centuries of Islamic civilization is analyzed.